Response of patients with chest tightness variant asthma with routine asthma treatment regimen: A 1‐year multicenter, prospective, real‐world study. Issue 5 (15th September 2020) - Yan, Fugui; Li, Wen; Guan, Wei‐jie; Chen, Min; Qiu, Chen; Tang, Wei; Liu, Xiansheng; Xiang, Xudong; Li, Jing; Jin, Meiling; Dai, Yuanrong; Chen, Ping; et al.
Abstract: Background: Asthmatic patients with chest tightness as their only presenting symptom (chest tightness variant asthma [CTVA]) have clinical characteristics of eosinophilic airway inflammation similar to those of classic asthma (CA); however, whether CTVA has similar response to antiasthma treatment as compared with CA remains unclear. Objective: The response of 76 CTVA patients to standard asthma treatments with inhaled corticosteroids with long‐acting beta‐agonists was explored in a 52‐week multicenter, prospective, real‐world study. Results: After 52 weeks of treatment with therapy regimens used for CA, the mean 5‐point Asthma Control Questionnaire (ACQ‐5) score decreased markedly from 1.38(first administration) to 0.71 (52 weeks, mean decrease: 0.674, 95%CI: 0.447‐0.900, P <.001).The mean asthma quality‐of‐life questionnaire (AQLQ) score increased from 5.77 (first administration) to 6.20 (52 weeks, mean increase: 0.441, 95% CI 0.258‐0.625, P <.001). Furthermore, at week 52, FVC, FEV1 %, the diurnal variation in PEFand the PD20‐FEV1 were significantly improved. Subgroup analysis revealed that the patients at first administration in the responsive group had higher ACQ‐5 scores than those in the nonresponsive group ( P  < .05). Conclusion: In conclusion, patients with CTVA had a good therapeutic response to the guideline‐recommended routine treatment (containing inhaled corticosteroids). The association between the treatment response and the severity of CTVA suggested that CTVA patients with higher ACQ‐5 scores had better therapeutic effects.